Evaluasi Dan Perbaikan Antarmuka Aplikasi Sistem Monitoring Pelanggan PT. PLN (PERSERO) Area Malang Menggunakan Metode Cognitive Walkthrough dan Heuristic Evaluation - Nizham Media Raziqi; Retno Indah Rokhmawati; Andi Reza Perdanakusuma (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Simpel Arema application (Sistem Monitoring Pelanggan Area Malang) is a web-based application developed by PT. PLN (Persero) Malang Area. Application is used to monitor customer data of PT. PLN (Persero) in Malang Regency. Based on the results of interview on the System Planning Supervisor, the application interface problems were found. This application has also never been evaluated before because it is still under development. Based on these problems, it is necessary to evaluate the Simplified Arema application specifically on the usability aspect. This evaluation was carried out using the Cognitive Walkhthrough method and Heuristic Evaluation, where evaluation was carried out by 3 subject matter experts, namely Malang Area PLN employees and 3 usability experts. The Cognitive Walkthrough evaluation results in the stage where usability problems are found in Simple Arema. While Heuristic Evaluation produces problems based on 10 heuristic principles and their severity. After evaluation, there were a total of 99 problems found in the Cognitive Walkthrough where 80% of the problems were found in Heuristic Evaluation too. While Heuristic Evaluation found 17 heuristic problems with the most problems being H-8 (Aestetic and minimalist design) with 23% of all Heuristic Evaluation problems. Based on the results of the evaluation, 19 recommendations for improvement were given, namely 17 improved interfaces and 2 system improvements. Based on recommendations for interface improvements, a prototype for Simple Arema interface was made. Then validation of the Simplified Arema interface repair prototype using the System Usability Scale (SUS) questionnaire to find out whether the improved Arema Simple interface is correct. Based on the results of the validation, the SUS score was obtained with a value of 83.3 and got the Acceptability Ranges level in the Acceptable category, Grade Scale in category B, Adjective in the Excellent category, and Percentile Rank at 80 - 90%.